عملية تحرير و لجوء الأمير محمد بن عبد الكريم الخطابي إلى مصر سنة 1947 - ميموني, رضا (جامعة الوادي - University of Eloued, 2018)
نهدف من خلال هذه الدراسة المتواضعة إلى تسليط الضوء على مرحلة مهمة من مراحل الكفاح ضد المستعمر الذي قاده زعماء الحركات التحررية المغاربية عقب الحرب العالمية الثانية بعد انتقالهم للقاهرة، وكان من أهم النشاطات التي قاموا بها هي ترتيب عملية تحرير ولجوء الأمير محمد بن عبد الكريم الخطابي لمصر، حيث أعطى هذا الأخير دفعة قوية لولوج العمل المسلح في المغرب العربي، وذلك من خلال استغلال خبرته السابقة في حرب الريف المغربية، والذي دون تردد بدأ منذ الوهلة الأولى لوصوله في العمل ورسم الخطط العسكرية، وكان أول شيء قام به هو تأسيس لجنة تحرير المغرب العربي سنة 1948، وشروعه مباشرة في تكوين مجموعة من الضباط لتشكيل النواة الأولى لجيش التحرير المغاربي، والذين كان لهم دورا كبيرا في قيادة العمليات العسكرية على الساحة المغاربية، وعليه سوف أحاول تتبع نشاط الأمير في القاهرة خاصة في الاتصالات التي قام بها مع ملوك ورؤساء الدول العربية من أجل قبول عدد من الشباب لتدريبهم وتوفير المراكز العسكرية لهم داخل بلدانهم. Summary: We aim through this modest study to shed the light on an important stage of the struggle against the colonial power, led by leaders of Maghreb liberation movements during the World War II after their moving to Cairo, where the most important activities have been made there to order the process of liberation and the resort of the Prince Mohammed bin Abdul Krim to Egypt , where he gave a strong push for entry of the military action in the Maghreb, by exploiting his previous experience in the Moroccan Rif war. From the moment of his arrival, he began, without hesitation , to work and draw military plans, and the first thing he had done is to establish a Committee for the Liberation of the Maghreb in 1948, and then started directly in the formation of a group of officers to form the nucleus of the Liberation Army of the Maghreb, and whom had a major role in leading the military operations on the scene of the Maghreb. Therefore, I will try to keep track of the Prince activity in Cairo, especially the contacts he made with the kings and heads of Arab states in order to accept a number of young people to train them and provide them with military centers within their own countries.
مقال
Keywords: عبد الكريم الخطابي، حرب الريف، المغرب العربي